2020
DOI: 10.21203/rs.3.rs-60610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Copper-oxide impregnated respiratory masks may significantly reduce the risk of SARS-CoV-2 cross-contamination

Abstract: The use of protective respiratory face masks has been adopted universally as an important measure in the fight against COVID-19. Masks become contaminated by symptomatic and asymptomatic SARS-CoV-2 infected individuals and the virus can remain viable on the surface of the masks for several days. Although the regular respiratory face masks are single use disposable masks, these masks are being largely reused and not often discarded after use by the general population. Mask touching during use, reuse and disposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…These masks presented excellent antiviral activity by inactivating the SARS-CoV-2 virus up to 99.9% with confirmation by serial PCR test and TCID 50 analysis. 100 A similar type of study was reported by Sunghoon and coworkers, in which a Cu-coated polypropylene layer was deposited on the surface of commercial KF94 masks using oxygen ion beam treatment and DC magnetron sputtering, as shown in Fig. 3(a).…”
Section: Cu-based Nanomaterialsmentioning
confidence: 63%
See 1 more Smart Citation
“…These masks presented excellent antiviral activity by inactivating the SARS-CoV-2 virus up to 99.9% with confirmation by serial PCR test and TCID 50 analysis. 100 A similar type of study was reported by Sunghoon and coworkers, in which a Cu-coated polypropylene layer was deposited on the surface of commercial KF94 masks using oxygen ion beam treatment and DC magnetron sputtering, as shown in Fig. 3(a).…”
Section: Cu-based Nanomaterialsmentioning
confidence: 63%
“…These masks presented excellent antiviral activity by inactivating the SARS-CoV-2 virus up to 99.9% with confirmation by serial PCR test and TCID 50 analysis. 100…”
Section: Coinage Metals and Their Antiviral Abilitymentioning
confidence: 99%
“…They observed a 75% reduction in viral load after 1 h incubation with SARS-CoV-2 [44]. Borkow reported a similar result for Cu coated masks with 99.9% inactivation of the pathogen within 1 min using TCID 50 and PCR assays [45]. Balagna et al developed a silver cluster/silica composite sputter coating onto a mask and observed a 2-to 4-log reduction in SARS-CoV-2 after 1.5 h incubation [46].…”
Section: Discussionmentioning
confidence: 83%
“…Different mechanisms of action of nanomaterials in consideration of Au and Ag nanoparticles with antimicrobial properties of nanoparticles, Cu antiviral effects, daylight or under UV light self-cleaning properties of TiO 2 and ZnO nanoparticles have been used. 137 , 149 152 Among these new types of nanomaterials are examples made with polymeric materials. Self-cleaning surfaces have been obtained thanks to the super-hydrophobic property added to the modification and design of nanomaterials.…”
Section: Nanomaterial-based Coatings For the Fight Against Covid-19mentioning
confidence: 99%